Precautionary motives in short-term cash management: Evidence from German POS transactions - Martina Eschelbach; Tobias Schmidt (Deutsche Bundesbank, 2013)
This paper empirically investigates whether individuals withhold a certain amount of cash for precautionary reasons at the point-of-sale (POS) in order to be able to cover future transactions that might have to be paid for in cash. Such behaviour is costly for consumers because it imposes additional restrictions on their choice of payment instrument at the POS. Based on the analysis of unique payment diary data compiled by the Bundesbank, we find that the probability of a transaction being settled in cash declines significantly as the amount of cash available at one's disposal decreases. This indicates that consumers do indeed refrain from parting with the entire amount of cash in their wallet. Further results suggest that this constraint could be relieved by facilitating access to cash or by promoting card acceptance.
Keywords: D12; E41; E58; 330; payment behaviour; demand for money; cash usage; payment cards; payment diaries